Differences in outcome of patients with cardiogenic shock associated with in-hospital or out-of-hospital cardiac arrest - Rusnak, Jonas; Schupp, Tobias; Weidner, Kathrin; Ruka, Marinela; Egner-Walter, Sascha; Forner, Jan; Bertsch, Thomas; Kittel, Maximilian; Mashayekhi, Kambis; Tajti, Péter; Ayoub, Mohamed; Behnes, Michael; et al. (Journal of Clinical Medicine, 2023)
Cardiogenic Shock (CS) complicated by in-hospital (IHCA) or out-of-hospital cardiac arrest (OHCA) has a poor outcome. However, studies regarding the prognostic differences between IHCA and OHCA in CS are limited. In this prospective, observational study, consecutive patients with CS were included in a monocentric registry from June 2019 to May 2021. The prognostic impact of IHCA and OHCA on 30-day all-cause mortality was tested within the entire group and in the subgroups of patients with acute myocardial infarction (AMI) and coronary artery disease (CAD). Statistical analyses included univariable t-test, Spearman’s correlation, Kaplan-Meier analyses, as well as uni- and multivariable Cox regression analyses. A total of 151 patients with CS and cardiac arrest were included. IHCA on ICU admission was associated with higher 30-day all-cause mortality compared to OHCA in univariable COX regression and Kaplan-Meier analyses. However, this association was solely driven by patients with AMI (77% vs. 63%; log rank p = 0.023), whereas IHCA was not associated with 30-day all-cause mortality in non-AMI patients (65% vs. 66%; log rank p = 0.780). This finding was confirmed in multivariable COX regression, in which IHCA was solely associated with higher 30-day all-cause mortality in patients with AMI (HR = 2.477; 95% CI 1.258-4.879; p = 0.009), whereas no significant association could be seen in the non-AMI group and in the subgroups of patients with and CAD. CS patients with IHCA showed significantly higher all-cause mortality at 30 days compared to patients with OHCA. This finding was primarily driven by a significant increase in all-cause mortality at 30 days in CS patients with AMI and IHCA, whereas no difference could be seen when differentiated by CAD.